Unilateral Primary Ovarian Lymphoma: A Case Report (Global Journal of Medical Research, 2020)
Involvement of the ovary by malignant lymphoma is well known as a late manifestation of disseminated nodal disease. But primary ovarian lymphoma as the initial manifestation is unusual. Histologically they are almost always of the non-Hodgkin's type. Primary ovarian lymphomas, account for only 0.5% of all non-Hodgkin lymphomas (NHLs) and 1.5% of all ovarian neoplasms. Previous studies of NHL involving gynecologic sites have shown that most (90%) NHLs involving the ovary are systemic tumors, of which ovarian involvement is only one aspect. In this article we report a case of unilateral primary ovarian NHL in a 35 yrs female patient. Consecutive histopathology and immunohistochemistry study revealed a primary Diffuse Large B-Cell Lymphoma (DLBCL) of ovary.